Design a Vital Sign Monitor for Body Temperature (Axilla) and Oxymetry Parameters - Mohamad Adam Firdaus; Andjar Pudji; Muhammad Ridha Mak'ruf (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA and IKATEMI, 2020)
In most hospitals, nurses routinely calculate and document primary vital signs for all patients 2-3 times per day to get information. Vital sign monitor is made for medical devices that can diagnose patients who need intensive care to determine patient needs. Some parameters were used oxygen saturation (SPO2), and body temperature. Therefore, the purpose of this study is to develop a vital sign monitor to record body temperature and oxygen saturation. This makes additional tasks are very important to be evaluated for medical staff and equipment manufacturers. This evaluation is needed to get the real condition of the patient. With the large number of patients who need evaluation, it is not possible to see the condition of some medical workers who work. This medical service is expected to reduce the workload of nurses with doctors and improve the quality of patient care. The great demand for these devices, mostly in intensive hospital rooms, is the basis for researching the output of data from multiple vital sensor monitor monitors to obtain accurate and precise outputs. The output of the two sensors is processed by Arduino Mega2560 and requested on a 5 inch TFT LCD in the form of body temperature and oxygen saturation. Comparison of module results with standard measuring instruments calibrated to reference this module is used for accurate and precise results. According to the assessment and reversing tool data with the dressing tool, the highest error value is 1%. With a maximum permitted permission of 5%.